PIPERINE IN THE PREVENTION OF THE DECREASED TAMOXIFEN SENSITIVITY IN MCF-7 BREAST CANCER CELL LINE - Kurniawan, Sandy Vitria; Sugiarti, Lies; Wanandi, Septelia Inawati; Louisa, Melva (International Journal of Applied Pharmaceutics, 2018)
Objective: This study was designed to analyze the role of piperine in modulating P-glycoprotein mRNA expression when added in combination with tamoxifen to breast cancer cells in culture. Methods: MCF-7 breast cancer cells were treated with 1 Î¼M tamoxifen with or without piperine (12.5, 25, or 50 Î¼M) or verapamil 50 Î¼M (P-glycoprotein inhibitor positive control) for up to 12 days. We assessed the cell viability and isolated total RNA from them. We quantified P-glycoprotein expressions using quantitative reverse transcription polymerase chain reaction. Results: Administration of various doses of piperine decreased MCF-7 breast cancer cell viability. Piperine, when given in combination with tamoxifen, decreased the expression of P-glycoprotein mRNA in cells compared with the expression in cells treated with tamoxifen only. The effects were shown to be dose dependent. Conclusion: Piperine prevents the development of breast cancer cell tamoxifen resistance, probably through its inhibition of P-glycoprotein expression.